STAKEHOLDERS IN THE ADVENTURE TOURISM DEVELOPMENT AT CURUG BIBIJILAN SUKABUMI REGENCY - Dr Eva Rachmawati; Muhamad Redito Gea Anjana (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Bibijlan waterfall is a destination that has the potential to be developed as an adventure tourism area. The development of tourism cannot be separated from the role of stakeholders. This study analyzes the current and potential stakeholders involved in developing adventure tourism in Curug Bibijilan and examines the expected involvement based on stakeholder analysis. The research was carried out using interviews, field observations, and literature studies. The analysis was carried out quantitatively and qualitatively. Stakeholder analysis is carried out to identify stakeholders, classify and map stakeholders, and analyze relationships between stakeholders. The results showed that ten identified stakeholders have been involved and have not been involved in developing adventure tourism in Curug Bibijilan. The stakeholders in the key player's (strong influence and high importance) group were Perhutani, Kompepar, and BAT. The stakeholders in the contex setter (Quadrants III - strong influence but low interest) was Kertaangsana Village. There were no identified stakeholders in quadrants II as the subject of the natural tourism development of Curug Bibijalan. Stakeholders identified in quadrant IV (crowds - low influence and low interest) include LMDH, the Tourism Office, the Transportation Service, the Water Service, and the Energy and Mineral Resources Office. There were three relationships between each identified stakeholder, namely communication, cooperation, and coordination. Key words: coordination, communication, natural tourism, stakeholder mapping